PENINGKATAN KEMAMPUAN MENULIS KARANGAN NARASI DENGAN LATIHAN MENJELASKAN ISI TABEL SISWA KELAS VII SMP MUHAMMADIYAH UJUNG GADING - Alpin Neli (PANTAK: Jurnal Penelitian Tindakan Kelas, 2024)
Based on the results of observations, it is known that the ability to write narrative essays of grade VII students of SMP Muhammadiyah Ujung Gading in the 2011-2012 Academic Year is still not satisfactory so that they have difficulty understanding the teaching materials presented by the teacher. For this reason, it is necessary to apply teaching strategies to improve students' abilities. One strategy that can attract students' interest in learning to improve their ability to write narrative essays is by practicing explaining the contents of a table. This means that before students are asked to produce narrative essays, they are first asked to explain the contents of a table. To find out the results of improving students' ability to write narrative essays by practicing explaining the contents of a table, research is needed. This study aims to find out data on improving the ability to write narrative essays by practicing explaining the contents of a table. The sample used in this activity was 40 students. The research instrument was writing narrative essays in the form of product essays or performance. After the data was analyzed, an increase was found, namely: the average pre-action score was 55, increasing in the first cycle to 61.375, increasing from the criteria of less to sufficient ability. The average score of the first cycle was 61.375, increasing in the second cycle to 73.13, the ability criteria increased to good, as well as learning completeness, there was an increase from 50% in the first cycle while the second cycle became 82.5%.